Desmicola lamdongensis sp. n. (Oxyuridomorpha: Thelastomatidae) from Vietnamese wood-burrowing cockroaches (Panesthiinae) - Sokolova, Elena A. (Zootaxa, 2019)
A new thelastomatid species, Desmicola lamdongensis sp. n. from the hindgut of Panesthiinae cockroaches collected in Bi Doup-Nui Ba National Park, Vietnam is described and illustrated. Males of the new species are characterized by seven to eight modified ventrally projected cuticular annuli on the posterior third of body and the straight spicule with a pointed distal tip; females are distinguished by the presence of tiny circular protrusions on the lip surface, three setiform sensilla as interlabial formations, horseshoe-shaped amphids and smooth oval egg-shells. D. lamdongensis sp. n. differs from the rest of Desmicola species in having males with ventrally projected cuticular annuli on the posterior body third vs. semispherical ventral cuticular protuberance. Similarly to females of other species of the genus, females of D. lamdongensis sp. n. possess a seminal receptacle only on the posterior branch of the reproductive system that allows them to produce a mixture of fertilized and non-fertilized eggs among their progeny. A key to species of Desmicola based on females is given. Posterovulva danieli Spiridonov & Ivanova, 1998 is regarded as D. danieli n. comb. in accordance with the latest revision of the genus (Adamson & Van Waerebeke 1992).